Tunable single longitudinal mode S-band fiber laser using a 3 m length of erbium-doped fiber - Ahmad, Harith; Zulkifli, Mohd Zamani; Latif, Amirah Abdul; Jemangin, M.H.; Chong, Su Sin; Harun, Sulaiman Wadi (Taylor & Francis, 2012)
In this paper a tunable single-longitudinal mode (SLM), short-wavelength band (S-band) fiber laser using a conventional erbium-doped fiber (EDF) with a length of 3m and a step index erbium dopant profile as opposed to the commonly used depressed cladding erbium-doped fiber (DC-EDF) is proposed and demonstrated. The proposed SLM fiber laser has a tuning range of 1496 to 1507nm in a ring configuration using two 0.15m of EDF which acts as saturable absorbers (SAs). The highest peak power measured is about 0.6dBm at a wavelength range of 1502 to 1507nm. The measured signal-to-noise ratio (SNR) is approximately 74dB for the same wavelength range. The line-width of the SLM output is measured to be 140kHz.